Temporal variations of 7Be and 210Pb activity concentrations in the atmospheric aerosols during 2018–2019 in Beijing, China and their correlations with meteorological parameters. (June 2023) - Wang, Huan; Meng, Qinghua; Ma, Yongzhong; Lou, Yun; Bai, Bin; Zhu, Weijie; Kong, Yuxia; Wang, Hongfang; Feng, Zechen; Zhai, Shuguang; Yu, Jun
Abstract: In order to establish a regional database on natural radioactivity, a series of measurements of 713 atmospheric aerosol samples collected on filters over a two-year period (2018–2019) in center of Beijing, northeastern China have been performed to analyze 7 Be and 210 Pb activity concentrations. The mean activity concentrations of 7 Be and 210 Pb were found to be 7.10 ± 2.44 mBq m −3 and 2.93 ± 1.52 mBq m −3, respectively. Both the radionuclides exhibited strong seasonal variations, with maximum concentration of 7 Be occurring in the spring and that of 210 Pb in the winter. The concentration of both the radionuclides was minimum in the rainy summer. Higher 7 Be concentration in the spring was mainly caused by the stratosphere to troposphere exchange. Higher 210 Pb concentration during winter was maybe attributed to the combustion processes in heating systems and the ingression of continental air masses resulted from winds originating from northwest. The dependence of the activity concentrations of 7 Be and 210 Pb with meteorological parameters such as rainfall, temperature, and humidity was studied through linear correlation analysis. Statistically significant negative correlations were observed between 7 Be and 210 Pb activity concentrations with rainfall, respectively, which suggested that the removal mechanisms of these two radionuclides were similar. Lead-210 showed statistically significant correlations with temperature, humidity and PM10 . A comparison of the data obtained in the present study for Beijing with the northern hemisphere literature values of 7 Be and 210 Pb in the atmospheric aerosols showed that the values were smaller than the ones observed in the present study. Overall, the study provides an improved understanding of the temporal variability and correlation of 7 Be and 210 Pb concentrations in the atmosphere in center of Beijing, northeastern China. Highlights: Regional database on 7 Be and 210 Pb activity concentrations in the atmospheric aerosols in center of Beijing was established. Rainfall is suggested as the major removal means for 7 Be and 210 Pb from the atmosphere. Causal factors for the temporal variability of 7 Be and 210 Pb activity concentrations were identified. Correlations of temperature, relative humidity and PM10 with 7 Be and 210 Pb were explored. Correlation between 7 Be and 210 Pb activity concentrations was studied.